READING SKILL AND SUPPRESSION REVISITED - Gernsbacher, Morton Ann (1995)
In a previous issue of Psychological Science, we (Gernsbacher, 1993) reported that less skilled readers are less able than more skilled readers to quickly suppress irrelevant information (e.g., the contextually inappropriate meaning of a homonym, such as the playing-card meaning of spade, in the sentence He dug with the spade, or the inappropriate form of a homophone, such as patience, in the sentence He had lots of patients). In the current research, we investigated a ramification of that finding: If less skilled readers are less able to suppress a contextually inappropriate meaning of a homonym, perhaps less skilled readers might be better than more skilled readers at comprehending puns. However, intuition and previous research suggest the contrary, as do the results of the research presented here. On a task that required accepting, rather than rejecting, a meaning of a homonym that was not implied by the sentence context, more skilled readers responded more rapidly than less skilled readers. In contrast, on a task that required accepting a meaning of a homonym that was implied by the sentence context, more and less skilled readers performed equally well. We conclude that more skilled readers are more able to rapidly accept inappropriate meanings of homonyms because they are more skilled at suppression (which in this case involves suppressing the appropriate meanings).